PENERAPAN LITERASI KEUANGAN MELALUI PROGRAM CHA-CHING IMPLIKASINYA TERHADAP KETERAMPILAN PENGAMBILAN KEPUTUSAN KEUANGAN SISWA - Lisa Ayu Pramesti; Urip Tisngati; Sugiyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Financial literacy is a basic need for individuals to avoid financial problems. This study aims to determine students' financial decision-making skills as an implication of the implementation of the Cha-Ching program. The type of research was descriptive qualitative. Informants consisted of a fifth-grade homeroom teacher, a program officer, and two fifth-grade students. The data collection method used indirect observation in the form of checklists and descriptions, Likert scale questionnaires, interviews, and documentation. Data analysis was qualitative through the stages of data reduction, data presentation, and verification/conclusion. The results of the study showed that: 1) the implementation of financial literacy through the Cha-Ching program was carried out in 6 stages, namely introduction, obtaining, saving, spending, donating, and conclusions, 2) the Cha-Ching program had implications for students' financial decision-making skills in the good category with an average questionnaire result of 3.84 which showed students were able to prioritize needs, were able to identify needs and desires, seek information, then make choices based on the information obtained, 3) the obstacles came from the teacher's side who had difficulty in delivering the material due to time constraints and the number of teacher activities. Students had difficulty memorizing and understanding the worksheets.